The running dream - Van Draanen, Wendelin (New York : Ember, 2012)
When a school bus accident leaves sixteen-year-old Jessica an amputee, she returns to school with a prosthetic limb and her track team finds a way to help rekindle her dream of running again.
Booklist
School Library Journal
Wilson's Junior High School
Booklist, January 2011
Bulletin (Center for Children's books), February 2011
Horn Book, March 2011
Keywords: Amputees -- Juvenile fiction; High schools -- Juvenile fiction; People with disabilities -- Juvenile fiction; Prosthesis -- Juvenile fiction; Running -- Juvenile fiction; Schools -- Juvenile fiction; Amputees -- Fiction; High schools -- Fiction; People with disabilities -- Fiction; Prosthesis -- Fiction; Running -- Fiction; Schools -- Fiction; Amputees -- Fiction; Artificial limbs -- Fiction; High schools -- Fiction; People with disabilities -- Fiction; Running -- Fiction; School stories